Unsupervised data imputation with multiple importance sampling variational autoencoders - Shenfen Kuang; Yewen Huang; Jie Song (Scientific Reports)
Abstract Recently, deep latent variable models have made significant progress in dealing with missing data problems, benefiting from their ability to capture intricate and non-linear relationships within the data. In this work, we further investigate the potential of Variational Autoencoders (VAEs) in addressing the uncertainty associated with missing data via a multiple importance sampling strategy. We propose a Missing data Multiple Importance Sampling Variational Auto-Encoder (MMISVAE) method to effectively model incomplete data. Our approach consists of a learning step and an imputation step. During the learning step, the mixture components are represented by multiple separate encoder networks, which are later combined through simple averaging to enhance the latent representation capabilities of the VAEs when dealing with incomplete data. The statistical model and variational distributions are iteratively updated by maximizing the Multiple Importance Sampling Evidence Lower Bound (MISELBO) on the joint log-likelihood. In the imputation step, missing data is estimated using conditional expectation through multiple importance resampling. We propose an efficient imputation algorithm that broadens the scope of Missing data Importance Weighted Auto-Encoder (MIWAE) by incorporating multiple proposal probability distributions and the resampling schema. One notable characteristic of our method is the complete unsupervised nature of both the learning and imputation processes. Through comprehensive experimental analysis, we present evidence of the effectiveness of our method in improving the imputation accuracy of incomplete data when compared to current state-of-the-art VAEs-based methods.